Dynamic properties of high-density low-alloy PM steels. (1st January 2017) - Zhang, Lin; Liu, Zhiwei; Sun, Haishen; Qin, Mingli; Qu, Xuanhui; Lyu, Yuanzhi
ABSTRACT: PM steels with density higher than 7.5 g cm −3 were prepared from binder-treated powder, and the effects of alloying elements and microstructure on dynamic performance were studied. Although the addition of 1.5 wt-% Cu improves the tensile strength, it impairs toughness of the alloy by the formation of low-toughness pearlite. The 0.5 wt-% Cr addition promotes the formation of Ni-rich martensite and bainite at the expense of pearlite, which is beneficial to strengthen and homogenise the microstructure. The 0.5Cr alloy exhibits improved tensile strength and fatigue strength without sacrificing impact toughness, which exhibits high potential to be used for dynamic and cyclic loading applications. The tensile strength and fatigue endurance strength under 10 7 cycles of 0.5Cr alloy achieve 1350 and 562 MPa respectively, and impact energy is as high as 21.1 J. The enhanced fatigue life is attributed to the high density, smaller pore size, rounder pores and composite-like microstructure.